2021
DOI: 10.1038/s41598-021-92368-9
|View full text |Cite
|
Sign up to set email alerts
|

Three distinct atmospheric circulation patterns associated with high temperature extremes in South Korea

Abstract: The negative impact of extreme high-temperature days (EHDs) on people’s livelihood has increased over the past decades. Therefore, an improved understanding of the fundamental mechanisms of EHDs is imperative to mitigate this impact. Herein, we classify the large-scale atmospheric circulation patterns associated with EHDs that occurred in South Korea from 1982 to 2018 using a self-organizing map (SOM) and investigate the dynamic mechanism for each cluster pattern through composite analysis. A common feature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…An increase in the intensity of the North Pacific High at 500 hPa height in July was revealed for the years 1977–2006 in the work (Shatilina & Anzhina, 2008), and the increase in surface pressure in July for 1975–2005 up to 1 hPa/10 years was identified in the work (Ippolitov et al, 2008). Kim et al (2021) found the North Pacific High extension at 850 hPa height from 1984 to 2018 years.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the intensity of the North Pacific High at 500 hPa height in July was revealed for the years 1977–2006 in the work (Shatilina & Anzhina, 2008), and the increase in surface pressure in July for 1975–2005 up to 1 hPa/10 years was identified in the work (Ippolitov et al, 2008). Kim et al (2021) found the North Pacific High extension at 850 hPa height from 1984 to 2018 years.…”
Section: Discussionmentioning
confidence: 99%
“…The SOM is implemented by the Python miniSOM library (Vettigli, 2021). The technical details have been described in many previous studies (Kim et al., 2021; Kohonen, 2013; Liu et al., 2006; Thompson et al., 2020), here we only provide a brief overview. The number of nodes (clusters) needs to be determined before implementing the SOM, and the Euclidean distance between the initiation nodes (randomly assigned in this study) and each input pattern is calculated to begin the iteration procedure, that is, the “training” of SOM.…”
Section: Methodsmentioning
confidence: 99%
“…In that sense, dimensionality reduction allows for a small number of patterns to be gleaned from a large dataset. Recent studies have shown that SOM is more effective than EOF analysis for capturing basic modes, especially for nonlinear processes [63,66]. In MHW research, the SOM is also considered an effective approach and is widely used.…”
Section: Self-organizing Mapsmentioning
confidence: 99%